2009
DOI: 10.1104/pp.109.142430
|View full text |Cite
|
Sign up to set email alerts
|

Studies of a Novel Cysteine Sulfoxide Lyase fromPetiveria alliacea: The First Heteromeric Alliinase

Abstract: A novel alliinase (EC 4.4.1.4) was detected and purified from the roots of the Amazonian medicinal plant Petiveria alliacea. The isolated enzyme is a heteropentameric glycoprotein composed of two a-subunits (68.1 kD each), one b-subunit (56.0 kD), one g-subunit (24.8 kD), and one d-subunit (13.9 kD). The two a-subunits are connected by a disulfide bridge, and both a-and b-subunits are glycosylated. The enzyme has an isoelectric point of 4.78 and pH and temperature optima of 8.0 and approximately 52°C, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 39 publications
(55 reference statements)
1
19
0
Order By: Relevance
“…It is well documented that glycoproteins as well as proteins with rigid disulfide linkages often exhibit anomalous migration profiles in SDS-PAGE (Segrest et al, 1971;Marciani and Papamatheakis, 1978). Additionally, we observed similar discrepancies with M r determination for P. alliacea alliinase, which shares with the P. alliacea LFS four of its five protein subunits (Musah et al, 2009). In-gel carbohydrate detection experiments showed that the a#-subunit is glycosylated (Fig.…”
Section: Discussionmentioning
confidence: 41%
See 3 more Smart Citations
“…It is well documented that glycoproteins as well as proteins with rigid disulfide linkages often exhibit anomalous migration profiles in SDS-PAGE (Segrest et al, 1971;Marciani and Papamatheakis, 1978). Additionally, we observed similar discrepancies with M r determination for P. alliacea alliinase, which shares with the P. alliacea LFS four of its five protein subunits (Musah et al, 2009). In-gel carbohydrate detection experiments showed that the a#-subunit is glycosylated (Fig.…”
Section: Discussionmentioning
confidence: 41%
“…Indeed, a single gene product can be a member of multiple complexes, such that the same protein or peptide can be utilized in different ways, depending upon the other peptides or proteins with which it is complexed. Surprisingly, even though the P. alliacea alliinase contains all the subunits of which the LFS is comprised, it is totally devoid of LFS activity (Musah et al, 2009). Likewise, the presence in the LFS of four of the five subunits contained in the P. alliacea alliinase does not render the LFS able to catalyze the breakdown of S-substituted Cys sulfoxides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The three-dimensional structure of the garlic alliinase at 1.5 Å resolution revealed that the active enzyme is a pyridoxal-5'-phosphate-dependent homodimeric glycoprotein (Kuettner et al, 2002), while another X-ray structure of the enzyme has improved the understanding of the pyridoxal phosphate binding to the active site (Shimon et al, 2007). A novel heteropentameric alliinase was detected and purified from the roots of the Amazonian medicinal plant Petiveria alliacea (Musah et al, 2009b), the same species displaying a novel lachrymatory factor synthase (LFS) (Musah et al, 2009a), an enzyme active only in the presence of alliinase (Eady et al, 2008). Another alliinase, purified from the bacterium Ensifer adaerens, displays a novel type of substrate specificity (Yutani et al, 2011).…”
Section: Introductionmentioning
confidence: 99%